2000
DOI: 10.3171/spi.2000.93.2.0294
|View full text |Cite
|
Sign up to set email alerts
|

Subacute posttraumatic ascending myelopathy after spinal cord injury

Abstract: ✓ Subacute posttraumatic ascending myelopathy is a rare disorder, unrelated to syrinx formation or mechanical instability, that may gradually emerge within the first 1 to 2 weeks after a spinal cord injury. The authors describe three patients with this syndrome and discuss its possible causes as well as its clinical presentation, imaging characteristics, treatment, and patient prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(77 citation statements)
references
References 19 publications
3
73
1
Order By: Relevance
“…However, a spinal angiogram was not performed on their patient. Angiographic study of the present patient, as well as the patient with an L1 injury reported by Belanger et al, 7 showed no evidence of thrombus in the GAA.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…However, a spinal angiogram was not performed on their patient. Angiographic study of the present patient, as well as the patient with an L1 injury reported by Belanger et al, 7 showed no evidence of thrombus in the GAA.…”
Section: Discussionsupporting
confidence: 71%
“…6 They all had fractures of the lower thoracic spine, except one patient with a T5 fracture. More recently, Belanger et al, 7 reported ascending neurological deficit in three patients with spine injuries, starting 7-13 days after injury. 7 Similar to the present patient, one of their cases had a Low baseline blood pressures were noted in their patient, and on postinjury day 12, she developed scapular pain and paresthesia in the upper limbs whenever she sat upright for physiotherapy.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…1 Several factors in our cases implicate a vascular mechanism, as with reports by Aito et al, 2 and Schmidt. 3 Case 1 had an injury at the thoraco-lumbar junction, where the artery of Adamkiewicz frequently enters, a potential area of intra-operative interference and ischaemia.…”
Section: Discussionsupporting
confidence: 86%
“…Subacute delayed ascending myelopathy (SDAM) is a rare, underrecognised neurological complication of spinal cord injury (SCI), defined as a delayed, subacute loss of spinal cord and nerve root function greater than four spinal segments above the original lesion unrelated to mechanical instability 1 (Supplementary Table).…”
Section: Introductionmentioning
confidence: 99%